Molecular phylogenetics facilitates the first historical biogeographic analysis of the hammerhead worms (Platyhelminthes: Tricladida: Bipaliinae), with the description of twelve new species and two new genera - Solà, Eduard; Sluys, Ronald; Riutort, Marta; Kawakatsu, Masaharu (Zootaxa, 2023)
The hammerhead worms constitute a land planarian subfamily (Platyhelminthes: Tricladida: Bipaliinae) that is popular among natural historians as well as citizen scientists due to their characteristic semi-lunar-shaped head, the striking colours of many species, and the worldwide presence of introduced species, which has raised much concern about their putative impact on the receiving ecosystems. Despite such current awareness, the majority of Bipaliinae species was described before the second half of the 20th century. Over the past few decades, description of new species has been rather scarce. In the present paper, we describe twelve new species and two new genera from Madagascar, Borneo, and Japan, mainly using specimens that form part of the collections of Naturalis Biodiversity Center, Leiden. Species identification has been based on morphology, inner anatomy, and, when available, molecular information. Our molecular phylogenetic tree suggests that either Malagasy or Bornean representatives form the sister-group to the rest of Bipaliinae. The phylogeny suggests also that the Bipaliinae comprises several new and, as yet, undescribed genera. Although the geographical origin of the subfamily is uncertain and may involve either Madagascar or the Bornean region, a molecular time-calibration of the phylogenetic tree indicated that the origin of the Bipaliinae may date back to about 253 Mya, placing its origin near the Permian-Triassic transition and, thus, on Pangea.